2017
DOI: 10.1007/s10886-017-0866-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leaf Volatiles of Ludwigia octovalvis (Jacq.) Raven in the Attraction of Altica cyanea (Weber) (Coleoptera: Chrysomelidae)

Abstract: Larvae and adults of Altica cyanea (Weber) (Coleoptera: Chrysomelidae) feed on the rice-field weed Ludwigia octovalvis (Jacq.) Raven (Onagraceae), commonly known as willow primrose, which is considered a biocontrol agent of the weed. Volatile organic compounds from undamaged plants, plants after 4, 12, and 36 h of continuous feeding by A. cyanea larvae or adult females and after mechanical damaging were identified by GC-MS and GC-FID analyses. Twenty nine compounds were identified from undamaged plants. 2Z-Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…We have previously demonstrated that herbivore-induced plant volatiles (HIPVs) from 10-leaf-stage L. octovalvis when fed by A. cyanea adults or larvae for 36 h were attractive to A. cyanea females compared to undamaged L. octovalvis (Mitra et al, 2017a). Furthermore, in our previous study, we identified 30 headspace compounds of L. octovalvis after 12 h of feeding by A. cyanea adults, and four more (geraniol, a-farnesene, 1-tridecanol, and farnesyl acetone) after 36 h of feeding (Mitra et al, 2017a). In the current study, we allowed A. cyanea adults to feed continuously for 48 h on L. octovalvis to see whether more feeding could induce extra volatile compounds.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that herbivore-induced plant volatiles (HIPVs) from 10-leaf-stage L. octovalvis when fed by A. cyanea adults or larvae for 36 h were attractive to A. cyanea females compared to undamaged L. octovalvis (Mitra et al, 2017a). Furthermore, in our previous study, we identified 30 headspace compounds of L. octovalvis after 12 h of feeding by A. cyanea adults, and four more (geraniol, a-farnesene, 1-tridecanol, and farnesyl acetone) after 36 h of feeding (Mitra et al, 2017a). In the current study, we allowed A. cyanea adults to feed continuously for 48 h on L. octovalvis to see whether more feeding could induce extra volatile compounds.…”
Section: Discussionmentioning
confidence: 99%
“…VOCs emitted from plants can serve as cues for host finding, feeding, and oviposition by herbivorous insects (Bruce et al, 2005;Bruce & Pickett, 2011). We have previously demonstrated that herbivore-induced plant volatiles (HIPVs) from 10-leaf-stage L. octovalvis when fed by A. cyanea adults or larvae for 36 h were attractive to A. cyanea females compared to undamaged L. octovalvis (Mitra et al, 2017a). Furthermore, in our previous study, we identified 30 headspace compounds of L. octovalvis after 12 h of feeding by A. cyanea adults, and four more (geraniol, a-farnesene, 1-tridecanol, and farnesyl acetone) after 36 h of feeding (Mitra et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations